Twenty two years of glory - Amy Zulaikha, Mohd Ali (UMPSA, 2024)
From its humble beginnings in 2002, As the sixteenth gem, a vison anew, Through trials and triumphs, it grew in grace, Nurtured by the loving hands of time's embrace